Knockout of calpain‐1 protects against high‐fat diet‐induced liver dysfunction in mouse through inhibiting oxidative stress and inflammation. Issue 1 (22nd December 2020) - Xu, Hao; Zhang, Li; Xu, Duowen; Deng, Weibo; Yang, Wenbao; Tang, Futian; Da, Mingxu
Abstract: The present study was designed to investigate the significance of calpain‐1 in the high‐fat diet (HFD)‐induced liver dysfunction and to explore the possible mechanism. C57 mice and calpain‐1 knockout (KO) mice were fed with standard diet ( SD ) or HFD, respectively, for 16 weeks. The activities of calpain, aspartate aminotransferase (AST), alanine aminotransferase (ALT), and superoxide dismutase (SOD) in serum and/or liver of mouse were measured. Lipid profiles in the serum and liver were examined. Contents of oxidized low‐density lipoprotein (oxLDL), malondialdehyde (MDA), tumor necrosis factor (TNF‐α), and interleukin‐6 (IL‐6) in serum or/and liver were detected. The results showed that compared with C57 mice fed with SD, HFD‐fed C57 mice showed the increased activities of AST and ALT in the serum, which was decreased in calpain‐1 KO mice fed with HFD. In addition, knockout of calpain‐1 decreased the contents of oxLDL, MDA, TNF‐α, and IL‐6, while increased SOD activity, in serum and/or liver. However, knockout of calpain‐1 had no effects on lipid profiles in both serum and liver. When fed with SD, all these parameters of C57 and calpain‐1 KO mice were comparable except for decreased calpain activity in the liver of calpain‐1 KO mice. The results suggested that knockout of calpain‐1 protects against HFD‐induced liver dysfunction through inhibiting oxidative stress and inflammation. Abstract : Knockout of calpain‐1 attenuates hyperlipidemia‐induced liver dysfunction of mice. Knockout of calpain‐1 decreases contents of oxidized low‐density lipoprotein and increased activity of superoxide dismutase. Knockout of calpain‐1 decreases tumor necrosis factor and interleukin‐6 contents